Predicting Treatment Response of Malignant Gliomas to Bevacizumab and Irinotecan by Imaging Proliferation With [18F] Fluorothymidine Positron Emission Tomography: A Pilot Study - Chen, Wei; Delaloye, Sibylle; Silverman, Daniel H.S.; Geist, Cheri; Czernin, Johannes; Sayre, James; Satyamurthy, Nagichettiar; Pope, Whitney; Lai, Albert; Phelps, Michael E.; Cloughesy, Timothy (Journal of clinical oncology, 2007)
Evaluation of treatment effects in malignant brain tumors is challenging because of the lack of reliable response predictors of tumor response. This study examines the predictive value of positron emission tomography (PET) using [18F] fluorothymidine (FLT), an imaging biomarker of cell proliferation, in patients with recurrent malignant gliomas treated with bevacizumab in combination with irinotecan. Patients with recurrent malignant gliomas treated with biweekly cycles of bevacizumab and irinotecan were prospectively studied with FLT-PET at baseline, after 1 to 2 weeks, and after 6 weeks from start of treatment. A more than 25% reduction in tumor FLT uptake as measured by standardized uptake value was defined as a metabolic response. FLT responses were compared with response as shown by magnetic resonance imaging (MRI) and patient survival. Twenty-one patients were included, and 19 were assessable for metabolic response evaluation with FLT-PET. There were nine responders (47%) and 10 nonresponders (53%). Metabolic responders survived three times as long as nonresponders (10.8 v 3.4 months; P = .003), and tended to have a prolonged progression-free survival (P = .061). Both early and later FLT-PET responses were more significant predictors of overall survival (1 to 2 weeks, P = .006; 6 weeks, P = .002), compared with the MRI responses (P = .060 for both 6-week and best responses). FLT-PET as an imaging biomarker seems to be predictive of overall survival in bevacizumab and irinotecan treatment of recurrent gliomas. Whether FLT-PET performed as early as 1 to 2 week after starting treatment is as predictive as the study indicates at 6 weeks warrants further investigation.